The Effectiveness of Benson’s Relaxation Therapy on Sleep Quality in Hemodialysis Patient: A Narrative Literature Review - Usa Sunairattanaporn; Pilaiwan Phuchum; Irma Darmawati (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2022)
Abstract Introduction: Patients on hemodialysis who have poor sleep quality suffer negative effects on their overall health and quality of life. Benson relaxation is a cost-effective therapy and an easy-to-do method for treating sleep disorders in hemodialysis patients. Objective: This narrative literature review aims to determine the efficacy of Benson's relaxation therapy on hemodialysis patients' sleep quality. Method: Searching databased conducted through PubMed, Science Direct, ProQuest, SAGE Journal, and EBSCO Host. Selection of published articles with a range of 2012-2022, free full text, randomized controlled trials, quasi-experiment, and published in the English language. A total of 441 articles were obtained, and 5 articles met the criteria included in this narrative literature review. An assessment is carried out using Prisma Procedure and the JBI format as critical appraisal tools to assist in assessing the trustworthiness, relevance, and results of published papers. Result: The results of this review showed that Benson's relaxation therapy works to help hemodialysis patients sleep better in four articles. This improvement is especially in sleep disturbance, daytime dysfunction, the use of sleep medication, and subjective sleep quality. Discussion: Benson's relaxation therapy combines deep breathing relaxation with the holding of certain beliefs; this can produce an optimal relaxation response, not only in the body but also in the mind. This relaxation response is necessary for entering the alpha wave, which is necessary for entering the first stage of sleep, and it will help patients have better quality sleep. AbstrakPendahuluan: Kualitas tidur yang buruk mempengaruhi status kesehatan dan kualitas hidup pasien hemodialisis. Relaksasi Benson adalah terapi hemat biaya dan metode yang mudah digunakan untuk mengobati gangguan tidur pada pasien hemodialisis. Tujuan: Literatur review naratif ini bertujuan untuk mengetahui efektivitas terapi relaksasi Benson terhadap kualitas tidur pada pasien hemodialisis. Metode: Pencarian database dilakukan melalui PubMed, Science Direct, ProQuest, SAGE Journal, dan EBSCO Host. Kriteria inklusi artikel yang diterbitkan dengan rentang tahun 2012-2022, teks lengkap gratis, penelitian randomized controlled trials, kuasi eksperimen, dan diterbitkan dalam bahasa Inggris. Didapatkan sejumlah 441 artikel, dan 5 artikel yang memenuhi kriteria dikaji dalam literatur review naratif ini. Penilaian dilakukan dengan menggunakan Prosedur Prisma dan format JBI sebagai alat penilaian kritis untuk membantu menilai keterpercayaan, relevansi, dan hasil makalah yang diterbitkan. Hasil: Hasil review ini menunjukkan bahwa terapi relaksasi Benson bekerja membantu pasien hemodialisis tidur lebih nyenyak dalam empat artikel. Peningkatan ini terutama pada gangguan tidur, disfungsi siang hari, penggunaan obat tidur, dan kualitas tidur subjektif. Diskusi: Terapi relaksasi Benson menggabungkan relaksasi nafas dalam dengan keyakinan yang dianut, hal ini dapat menghasilkan respon relaksasi yang optimal, tidak hanya fisik tetapi juga mental. Respon relaksasi ini diperlukan untuk memasuki gelombang alfa untuk memasuki tahap pertama tidur dan akan membantu kualitas tidur pada pasien